2012
DOI: 10.1097/aap.0b013e31824889b6
|View full text |Cite
|
Sign up to set email alerts
|

Primary Payer Status Is Associated With the Use of Nerve Block Placement for Ambulatory Orthopedic Surgery

Abstract: Introduction Although more than 30 million patients in the United States undergo ambulatory surgery each year, it remains unclear what percentage of these patients receive a perioperative nerve block. We reviewed data from the 2006 National Survey of Ambulatory Surgery (NSAS) to determine the demographic, socioeconomic, geographic, and clinical factors associated with the likelihood of nerve block placement for ambulatory orthopedic surgery. The primary outcome of interest was the association between primary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Tighe et al analyzed 3.9 million weighted ambulatory orthopaedic surgery procedures and found that after controlling for covariates, privately-insured patients were 2.62 times more likely to receive a nerve block for analgesic relief than patients with self-care or charity reimbursement. 49 This phenomenon is not unique to orthopaedics, as numerous obstetrics studies have reported that private insurance and higher levels of maternal education are associated with greater rates of epidural anesthesia administration during labor and delivery. 50,51 In our unadjusted analysis, isolated RA was almost exclusively performed at urban, teaching hospitalsa trend that has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tighe et al analyzed 3.9 million weighted ambulatory orthopaedic surgery procedures and found that after controlling for covariates, privately-insured patients were 2.62 times more likely to receive a nerve block for analgesic relief than patients with self-care or charity reimbursement. 49 This phenomenon is not unique to orthopaedics, as numerous obstetrics studies have reported that private insurance and higher levels of maternal education are associated with greater rates of epidural anesthesia administration during labor and delivery. 50,51 In our unadjusted analysis, isolated RA was almost exclusively performed at urban, teaching hospitalsa trend that has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 In our unadjusted analysis, isolated RA was almost exclusively performed at urban, teaching hospitalsa trend that has been previously reported. 52,49 The finding is likely associated with the overwhelming predominance of academic medical centers in urban regions, and the trend of isolated RA being performed primarily at academic centers where fellowship-trained faculty tend to practice. 49,53 With the exception of obesity, major medical comorbidities were more prevalent in patients receiving GA, a finding previously reported in TJA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using block areas with registered nurses trained to assist with regional anesthesia reduces operating room time and increases throughput [65][66][67][68][69][70][71][72]. The use of peripheral regional anesthesia reduces how long patients stay in the phase I post-anesthesia care unit [69,73,74] and their time to discharge [75]. Monitored anesthesia care also facilitates bypass of the phase I post-anesthesia care unit [76][77][78].…”
Section: Ambulatory Surgery Without Aerosol Production Without Genermentioning
confidence: 99%
“…42 In addition, the fact that most insurance plans will cover a regional nerve block in shoulder arthroscopy cases might have helped in the expansion of this pain management technique. 35 Finally, regional nerve blocks are generally safe, and patients undergoing shoulder arthroscopy seem to be satisfied with their use in clinical practice. 7 Similar to our methodology, previous studies have extracted data from the Humana database to identify the trends in perioperative opioid prescription in patients undergoing shoulder procedures and to explore the risk factors for increased postoperative opioid demand.…”
Section: Discussionmentioning
confidence: 99%